Thinking Twice: The Weinberger Doctrine and the Lessons of Vietnam - Alterman, Eric R. (Tufts Archival Research Center, 2005)
Volume 10, Issue 1. Winter Debate is still raging over the Vietnam experience: why did we get involved, why did we lose, and what does our military failure mean for the future of U.S. foreign policy? In this article, Eric R. Alterman argues that, though consensus on these questions remains elusive within the U.S. civilian community, the outlines of an emerging consensus are evident within the U.S. armed forces. Secretary of Defense Caspar Weinberger's now- famous speech on the six essential conditions necessary before war should be fought reflects this military consensus. Mr. Alterman analyzes each of Weinberger's points in the context of military conclusions from the Vietnam era. He concludes that the lessons from Vietnam drawn by the armed forces can be seen clearly in the military's restraining role in recent U.S. policy toward Central America and Lebanon.